ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEGAGALAN IPO (APLIKASI SURVIVAL ANALAYSIS) - Hartanto, Luthfi; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2014)
The purpose of this study was examine the effect of the failure of the companyâ€™sIPO. Failure IPO seen from the decline in the stock price by 50% over Â 5 years (60 months). The depedent variabel in this study is the failure of the companyâ€™s IPO that was measure by the time between IPO to failure. The independent variabel in this study is the firm age, firm size, initial return, business risk and the percentage of stock offerings.The study uses data from the annual report companies with listing on the Indonesia Stock Exchange in 2006-2009. Total of samples in this study is 59 companies. This study uses survival analysis method and cox regression analysis as the tool of survival analysis.The results of this study showed that firm age affect on IPO failure of a company, althought not significantly. Firm size and initial return affect of IPO failure of a company and significantly. Business risks affect the IPO failure of a company, althought not significantly. Percentage share offer does not affect the failure, althought not significantly.